Ontology negotiation: Knowledge interchange between distributed ontologies through agent negotiation. (23rd June 2019) - Zhu, Junwu; Teng, Ling; Lu, Huimin; Shi, Jieke; Li, Bin
Summary: With the proliferation of knowledge source on the internet as well as the widely professional agents, the knowledge interchange is drawing much attention. Ontology is recognized as the crucial technology due to their nature of sharing, formalization, and conceptualization to integrate and share the knowledge. In this paper, by interpreting and negotiating the communication content, a unified understanding of knowledge is formed; then, we can realize the interoperability between ontologies. We have developed the ontology automatic negotiation by agent elect protocol (AEP) to elect optimal participants and encourage agents to obey the protocol, concept mapping protocol (CMP) to find the corresponding concept mappings with the highest relevancy, and in addition, agent negotiation protocol (ANP). In ANP, we define the simultaneous negotiation protocol and agents' strategies to combine distributed ontologies interchange with agent negotiation. Finally, the implementation and preliminary results are given to verify the validity of the proposed ontology negotiation.